Axial strength of CFRP strengthened concrete columns under elevated humid environments - Samsuddin, Mohd Zuwairi; Muhammad Rashid, Raizal Saifulnaz; Aboutaha, Riyad (2015)
Carbon fiber reinforced polymer (CFRP) has been proven to be effective in increasing the axial strength of concrete columns. However, there is very limited data on the effects of high humidity on the performance of CFRP strengthened columns. In addition, humidity has direct impact on the strength of concrete material. This paper presents the results of an experimental investigation of short concrete columns strengthened with transverse CFRP wrapping, under various humid conditions. A large series of concrete cylinder to stimulate as concrete column were strengthened and tested at 60%, 70%, 80%, and 90% relative humidity. Specimens were stored for at least three weeks at every specified constant humidity level, then tested under pure axial loads. The axial load and longitudinal deformations of each specimen were measured during the test. Test results suggest that an increase in humidity will lead to a reduction in the axial strength of CFRP strengthened concrete columns. An equation to predict compressive strength of CFRP - confined concrete column exposed to high humidity was established. Details of strengthening system, as well as the experimental program, and test results will be presented.